Analysis of IgE turnover in non-sensitized and sensitized rats - Kazuhiko Hanashiro; Yoshihiro Tokeshi; Toshiyuki Nakasone; Masanori Sunagawa; Mariko Nakamura; Tadayoshi Kosugi (Mediators of Inflammation)
Background: Although the levels of immunoglobulin E (IgE) in the circulating blood are often elevated in patients with allergic diseases, such levels cannot always be considered as pathognomonic signs of allergy. The induction of allergic reactions in the tissue was inferred to be related to the amount of IgE passing through the vascular wall.